Enhancing Students’ Soft Skills through a Project Based Digital Entrepreneurship Model in a Primary Edupreneurship Course - Raras Setyo Retno; Tiara Intan Cahyaningtyas; Mutia Gama Mayoni; Desi Ana Puspitasari (Universitas Pendidikan Ganesha, 2026)
Entrepreneurship education in higher education remains largely theoretical, limiting students’ soft-skill development. Opportunities to foster creativity, collaboration, communication, and problem-solving through authentic learning experiences remain limited. This study aims to analyze the effectiveness of the Project Based Digitalpreneurship model in improving students’ soft skills in the Primary Edupreneurship course. The study employed a quantitative approach with a pre experimental one group pretest posttest design. The research subjects consisted of 30 sixth semester students selected using a purposive sampling technique. Data were collected through observation, questionnaires, and documentation using a soft skills assessment rubric covering aspects of self confidence, creativity and innovation, teamwork, and performance. Data analysis was conducted using descriptive statistics, N-gain calculation, and paired sample t-test analysis. The results showed that students’ average scores increased from 78 in the pretest to 86 in the posttest, with an N-gain value of 0.37 (moderate category). The results of the paired sample t-test indicated a significance value of 0.001 (p < 0.05), demonstrating a significant improvement in students’ soft skills after the implementation of the learning model. The study concludes that the Project Based Digitalpreneurship model is effective in enhancing students’ soft skills in entrepreneurship learning. The implication of this study suggests that the model has the potential to be implemented as an innovative learning alternative to support the development of soft skills and entrepreneurial competencies in teacher education programs.